Fundamentals of Value Based Management in practice of Quality management - Katarzyna Szczepańska (Contemporary Economics)
The article discusses the practical aspects of using the theory of value management in quality management. Presents the essence of value based management (VBM) as a background of reflection on its links with quality management. Coherence of the concept in practice, been reviewed in the author’s own studies. The discovery of absence of sufficient procedural structure of the metrics of an economic – financial, to measure the value of the quality management system, points to a gap between the theoretical and practical considerations in managing the value of the company quality management system.